Analisis Miskonsepsi Siswa dengan Menggunakan Tes Diagnostik Two-Tier Multiple Choice pada Materi Struktur Atom di SMA NEGERI 1 Remboken - Rivya Tamungku; Djefry Tani; Jeanne Tuerah (Oxygenius Journal Of Chemistry Education, 2019)
Misconceptions can be in the form of initial concepts, mistakes, incorrect relationships between concepts, intuitive ideas or naive views. From the explanation that has been described misconception is interpreted as an initial concept owned by students that is not in accordance with the generally accepted explanation as a result of the experience constructed by students. Misconception can also be called an alternative concept. This study aims to determine the misconceptions of Class X students of Natural Sciences 2 of SMA Negeri 1 Remboken on atomic structure material. Data collection uses questions in the form of a two-tier diagnostic test, which was tested on 20 students. From the results of the study concluded that students who understood the concept of 82.75%, and students who experienced misconceptions as much as 11.25% while students who did not understand the concept of 6% in the Atomic Structure material.